Morphological differentiation of Pennahia aneus (Bloch, 1793) populations from Northern Peninsular Malaysia using geometric morphometrics - JOLLY BABANGIDA KACHI; KHALED BINASHIKHBUBKR; DARLINA MD NAIM (Nusantara Bioscience, 2025)
Abstract. Kachi JB, Binashikhbubkr K, Naim DM. 2025. Morphological differentiation of Pennahia aneus (Bloch, 1793) populations from Northern Peninsular Malaysia using geometric morphometrics. Nusantara Bioscience 17: 30-38. The investigation of geometric morphometrics offers evidence for the adaptive traits shown by fish in response to their aquatic environment, which may be attributed to evolutionary processes. The examination of body morphometry has significant value in assessing the structure of fish populations, which is a fundamental necessity for the implementation of conservation measures and the management of fisheries in a sustainable manner. The study used geometric morphometrics to differentiate three populations of Pennahia aneus from Northern Peninsular Malaysia. A sum of 110 samples were obtained from Pulau Pinang, Kedah, and Perak states in Malaysia. Photographs of fish samples were taken, and 13 homologous landmarks were digitized using the tpsUtil and tpsDig2 software. All data were analyzed using multivariate statistical tests such as canonical variate analysis, cluster analysis, principal component analysis, and discriminant function analysis. Results showed significant morphological variations among the population of P. aneus with two morphological groups: Batu Maung group and Pantai Remis and Kuala Kedah group. The overall reclassification grouping for the populations of P. aneus in this study was 67.3% successful. These findings are crucial for conservation and management efforts and contribute to formulating efficient conservation policies to maintain the species populations in Northern Peninsular Malaysia, highlighting the potential impact of this research on future conservation policies. Further investigations in terms of expanding the study scope and application of molecular tools will give a holistic understanding of P. aneus population structure in Malaysia. This study represents the first to compare morphological differences in P. aneus populations from Malaysian waters using geometric morphometric analysis.